2014
DOI: 10.1038/srep05815
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Heterogeneous Stem Cell Differentiation on a Shape Memory Hydrogel Surface

Abstract: The success of stem cell therapies is highly dependent on the ability to control their programmed differentiation. So far, it is commonly believed that the differentiation behavior of stem cells is supposed to be identical when they are cultured on the same homogeneous platform. However, in this report, we show that this is not always true. By utilizing a double-ion-triggered shape memory effect, the pre-seeded hMSCs were controllably located in different growth positions. Here, we demonstrate for the first ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 41 publications
0
52
0
Order By: Relevance
“…17 These characteristic peaks suggest the formation of PVDT-PAA hydrogels via photo-polymerization. 17 These characteristic peaks suggest the formation of PVDT-PAA hydrogels via photo-polymerization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 These characteristic peaks suggest the formation of PVDT-PAA hydrogels via photo-polymerization. 17 These characteristic peaks suggest the formation of PVDT-PAA hydrogels via photo-polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…14 The SM behavior originates from the high complexation ability of oxidized ferric ions with phosphate groups, which served as the reversible physical crosslinking that could firmly lock the temporary shape. 17 We demonstrated that the differentiation behavior of hMSCs was highly sensitive to their growth position on the hydrogel scaffold. 3 In developing new shape memory hydrogels, it is of great importance to explore SM hydrogels in biomedical applications.…”
Section: Introductionmentioning
confidence: 86%
“…Although, shape-memory polymers (SMPs) have been widely studied and expected to hold great potential applications, [41][42][43] few SMPs can really be used in living biological systems, because the external stimulus may damage surrounding tissues and cells. Besides the above mentioned excellent mechanical performance, another intriguing character of the present PUUS materials is their water-responsive shape-memory behaviours.…”
Section: Figmentioning
confidence: 99%
“…Moreover, owing to the reversible physical crosslinking from DAT-DAT H-bonding or CN-CN dipole-dipole interaction, the PVDTbased and DDR hydrogels demonstrated stimuli-responsiveness and shape memory behaviors in response to the variation in pH, [ 8 ] reductive medium, [ 24 ] and concentration of metal ion. [ 21,22,25 ] Also, by copolymerizing N-isopropylacrylamide (NIPAAm) or spiropyran monomer, these PVDT-based hydrogels were capable of responding to the thermal stimulus or light stimulus, respectively, without worsening their high strengths. [ 18,26,27 ] Nonetheless, these hydrogels were poor in dissipating external energy, and in particular sensitive to the notches preformed.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Recently, we designed and constructed high strength stimuli-responsive hydrogels based on strong intermolecular hydrogen bonding of diaminotriazine (DAT) residues in poly(vinyl diaminotriazine) (PVDT) [ 8,[17][18][19][20] and CN-CN dipole-dipole reinforcement (DDR) in polyacrylonitrile. [21][22][23] These hydrogels turned out to exhibit high A double hydrogen bonding (DHB) hydrogel is constructed by copolymerization of 2-vinyl-4,6-diamino-1,3,5-triazine (hydrophobic hydrogen bonding monomer) and N , N -dimethylacrylamide (hydrophilic hydrogen bonding monomer) with polyethylene glycol diacrylates. The DHB hydrogels demonstrate tunable robust mechanical properties by varying the ratio of hydrogen bonding monomer or crosslinker.…”
mentioning
confidence: 99%